2004
DOI: 10.1590/s0101-81752004000300008
|View full text |Cite
|
Sign up to set email alerts
|

Macrozooplâncton da Zona Econômica Exclusiva do Nordeste do Brasil (segunda expedição oceanográfica - REVIZEE/NE II) com ênfase em Copepoda (Crustacea)

Abstract: . ustacea). ustacea). ustacea). ustacea). The present study was performed with the objective to characterise the density, relative abundance, frequency of occurrence, specific diversity and species associations of the oceanic macrozooplankton of the "Exclusive Economic Zone". The area under investigation is located between 7º28'56"S -34º32'45"W and 3º21'08"S -38º40'29"W, sampled during the second oceanographic expedition REVIZEE/NE on board OV Antares of the Brazilian Navy. Twenty-one samples were taken with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 13 publications
(10 reference statements)
3
27
1
1
Order By: Relevance
“…Shannon's diversity is considered high when it is above 3, average, between 2 and 3, low, between 1 and 2, and very low when under 1 (Cavalcanti and Larrazábal, 2004 When considering the number of individuals found on each environment (Table 2), it is observed that, during the rainy season, the environment that stood out the most was the annual maize culture, in which the monoculture management characteristics favor the occurrence of certain weed species, mainly from the Amaranthaceae, Asteraceae and Solanaceae families, on the seed bank; however, the diversity of species was lower than on the perennial culture area.…”
Section: Resultsmentioning
confidence: 99%
“…Shannon's diversity is considered high when it is above 3, average, between 2 and 3, low, between 1 and 2, and very low when under 1 (Cavalcanti and Larrazábal, 2004 When considering the number of individuals found on each environment (Table 2), it is observed that, during the rainy season, the environment that stood out the most was the annual maize culture, in which the monoculture management characteristics favor the occurrence of certain weed species, mainly from the Amaranthaceae, Asteraceae and Solanaceae families, on the seed bank; however, the diversity of species was lower than on the perennial culture area.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with Cavalcanti and Larrazábal (2004), the Shannon diversity can be assessed as very low (values lower than 1.0 bits.ind.…”
Section: Discussionmentioning
confidence: 99%
“…The Shannon-Wiener diversity is considered high when it is above 3, average between 2 and 3, low between 1 and 2 and very low less than 1 (Cavalcanti & Larrazábal, 2004).…”
Section: Although Management Practicesmentioning
confidence: 99%